Problems of the knowledge of nature as God's creation in the documents of the Second Vatican Council - Pryshlyak, Mykola (Ukrai͏̈ns'ke relihijeznavstvo, 2013)
The need to study the documents of the Second Vatican Council on the preservation of the environment is conditioned by concrete changes in modern society, manifested in the escalation of conflicts in relations between man and nature, the transition to the post-industrial stage of development of society, globalization. Along with the positive effects and benefits of civilization, there are also dangers, including environmental ones. In modern Ukraine, the processes associated with the transition to a market economy, the adoption of the values ​​of Western society, which require transformation in all spheres of social life. These changes should be based on the existing spiritual and intellectual traditions of society and provide for the resolution of environmental problems as a priority task for the further development of society.